2021
DOI: 10.1002/tqem.21739
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of combined mixture and process variables for the pyrolysis oil yield from co‐pyrolysis of polymeric wastes

Abstract: The combined mixture process variable approach for optimization and prediction of oil yield in co‐pyrolysis of polymeric wastes was investigated in this study using I‐optimal design. The components mixture investigated were low‐density polyethylene (LDPE), polystyrene (PS), and polyethylene terephthalate (PET), whereas the process variables were temperature and residence time. Thirty experimental runs were developed using the I‐optimality criterion to investigate the effect of interaction between the mixture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Such hydrocarbon content increase is accompanied by lower acids, improving the bio-oil quality by increasing stability and calorific value and reducing corrosion problems. An elemental analysis performed on the mixture with 40% HDPE reported +14% for carbon and −50% for oxygen and a calorific value of 42 MJ/kg (43% higher than calculated), similar to the commercial diesel reported values [ 33 , 37 ].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Such hydrocarbon content increase is accompanied by lower acids, improving the bio-oil quality by increasing stability and calorific value and reducing corrosion problems. An elemental analysis performed on the mixture with 40% HDPE reported +14% for carbon and −50% for oxygen and a calorific value of 42 MJ/kg (43% higher than calculated), similar to the commercial diesel reported values [ 33 , 37 ].…”
Section: Resultssupporting
confidence: 64%
“…Conversely, xylene, toluene, and benzene exhibited decreased levels compared to individual pyrolysis [ 32 ]. Additionally, Oladunni et al, 2021 reported the presence of unsaturated hydrocarbons (C=C) and aromatic hydrocarbons in the pyrolysis of LDPE, along with the detection of free OH radicals, reactive carbonyl groups, aldehydes, ketones, esters, and conjugated carboxylic acids through FTIR analysis [ 33 ]. This finding is supported by a previous study by Kayacan and Dogan (2008), who observed that aliphatic (C-C and C-H) and CH2 groups were the predominant components in the pyrolysis of raw and waste HDPE and LDPE [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oil fraction can be then valorized as fuels or reused as monomers after steamcracking. Studies have shown that the proportions of each fraction are directly related to the reactor type and operating conditions set as temperature, pressure, fluidized gas flow rate, or residence time. It has also been shown that the use of catalysts impacts the fraction ratio . Moreover, the composition of raw plastic material is also a determining factor .…”
Section: Introductionmentioning
confidence: 99%